2007
DOI: 10.1002/ajmg.a.31601
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a 16 Mb interstitial chromosome 7q21 deletion by tiling path array CGH

Abstract: We report on a 42-year-old female patient with an interstitial 16 Mb deletion in 7q21.1-21.3 and a balanced reciprocal translocation between chromosomes 6 and 7 [karyotype 46,XX,t(6;7)(q23.3;q32.3)del(7)(q21.1q21.3)de novo]. We characterized the size and position of the deletion by tiling path array comparative genomic hybridization (CGH), and we mapped the translocation breakpoints on chromosomes 6 and 7 by FISH. The clinical features of this patient-severe mental retardation, short stature, microcephaly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…1D) [3,4,5,6]. The phenotypic findings of our case were similar to previous cases and included prenatal growth retardation, facial dysplasia, and hand/foot malformations (Table 1).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…1D) [3,4,5,6]. The phenotypic findings of our case were similar to previous cases and included prenatal growth retardation, facial dysplasia, and hand/foot malformations (Table 1).…”
Section: Discussionsupporting
confidence: 84%
“…Although several 7q deletion cases involving 7q21.13q22.1 have been reported, most of them involved a broader region than 7q21.13q22.1, and only a few cases were able to delineate the precise chromosomal breakpoint by high-resolution microarray analysis (Table 1) [3,4,5,6]. Since the emergence of high-resolution cytogenetic techniques in clinical diagnostics, the identification of more detailed breakpoints and the subsequent reestablishment of phenotype-genotype correlations become possible.…”
Section: Discussionmentioning
confidence: 99%
“…Addition-ally, breakpoints analysis revealed that the proximal breakpoint of the present deletion lies just 88 kb downstream of the DLX5 gene. Because haploinsufficiency for DLX5 and DLX6 genes appears to be responsible for ectrodactyly [Scherer et al, 1994;van Silfhout et al, 2009], our observation indirectly confirms the exclusion of the CUX1 gene (as suggested by Bernardini et al [2008]) and potential regulatory elements (as suggested by Tzschach et al [2007]) downstream of DLX5 and ACN9 (between RP11-800O14 and D7S618) in determining such a limb defect.…”
Section: Discussionsupporting
confidence: 74%
“…1,7 It is not known whether the same gene defect is responsible for both SHFM and deafness, or if two different genes in the SHFM1 region are involved. 11,25 In our third patient, PDD-NOS has been diagnosed. A relation between SHFM and autism has not been described previously.…”
Section: Review Of Literature and Discussionmentioning
confidence: 59%